A STUDY ON MALE SEXUAL IMAGERY IN ADVERTISING: EFFECTS, PERSPECTIVE & SOCIAL IMPLICATIONS - Harshita Singh, Dr. Bhargavi D Hemmige (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This research paper examines the prominent but underexplored phenomenon of male sexual imagery in advertising, focusing on its multifaceted effects, societal perspectives, and wide-ranging social implications. The study is guided by three principal objectives - To evaluate how consumer attitudes and behaviors are affected by images of men being sexually explicit in advertising. This objective is to clarify how the representation of male sexuality affects consumer perceptions, preferences, and buying decisions through empirical research and content analysis. To look at how different stakeholders, such as consumers, advertisers, and advocacy groups, feel about the usage of male sexual images in advertising. To learn more about these stakeholders' motivations, worries, and ethical considerations, qualitative research techniques will be used. To examine how male sexual imagery in advertising affects society as a whole, with a focus on how it affects how men and women interact with one another today. This minor research project will investigate how such imagery interacts with changing cultural norms and adds to the debates around sexual objectification, gender equality, and body image. By focusing on these goals, this research article contributes to a thorough understanding of the intricate interactions between male sexual imagery and advertising and provides insights into its effects on both people and society as a whole. The results are intended to guide advertising practices, spark debate, and promote a sophisticated understanding of the impact and obligations related to the use of male sexual images in the field of advertising.